(untitled) (Revista Apotheke, 2021)
The following communication tries to show, making an analysis of the philosophy of the experience of John Dewey, that some dichotomies would be unfounded. These dichotomies make us see scientific knowledge, ethics, aesthetics and questions of social order as sectors with some peripheral areas in conflict, but essentially separate. Dewey offers us a different way of looking at this question by applying scientific methods to the human and social sciences. Dewey’s reconstruction of the experience has allowed him to take an important step in reestablishing transactional continuity and thus show how practical and theoretical judgments, despite all their differences, can be reduced to the same common pattern. Therefore, paradigmatic value judgments are capable of being rationally-experimentally guaranteed as are means-consequences judgments. The reconstruction of experience, therefore, is what allows Dewey to unite theory (and his judgments) and practice (with his own), shortening the difference between science, art and morality, as well as establishing contact bridges between them.